The Efficacy and Safety of Leflunomide for the Treatment of Lupus Nephritis in Chinese Patients: Systematic Review and Meta-Analysis. - Heng Cao; Yuefeng Rao; Lin Liu; Jin Lin; Hongyu Yang; Xingguo Zhang; Zhong Chen (PLoS ONE)
Objective To evaluate the clinical efficacy and safety of leflunomide as a new immunosuppressive medicine in lupus nephritis (LN) through a meta-analysis. Methods A systematic review evaluating the efficacy and safety of leflunomide compared with cyclophosphamide in adult patients with LN was performed. Data from relevant randomized controlled trials (RCTs) performed before December 2014 was collected from several databases (PubMed, Embase, Cochrane Library, CNKI and CBM). No language restrictions were applied. Efficacy outcomes included overall remission, SLE Disease Activity Index (SLEDAI) score, 24-hour proteinuria and serum creatinine. Safety data were analyzed. The effects of treatment on these outcomes were summarized as relative risks (RRs) with 95% confidence intervals (CIs) and mean differences were pooled using a fixed or random effects model. Results Eleven RCTs with Jadad score of 3 or greater were identified and included a total of 254 patients. Cyclophosphamide was served as the control drug in all trials. The SLEDAI score, urine protein level and serum creatinine decreased significantly following leflunomide treatment (P<0.05). Leflunomide was superior to cyclophosphamide in achieving complete and total remission, but no difference in SLEDAI score was found between these two treatments (P>0.05). Additionally, patients receiving leflunomide treatment showed favorable renal function profiles, especially regarding the 24-hour proteinuria (mean difference: -0.58, 95%CI: -0.78~-0.37, P<0.01) and serum creatinine (mean difference: -0.20, 95%CI: -0.39~-0.01, P<0.05). In the safety comparison, leflunomide was safer than cyclophosphamide regarding adverse drug reactions (ADRs), including liver damage (RR = 0.53, 95%CI: 0.33~0.87, P<0.05), alopecia (RR = 0.38, 95%CI: 0.17~0.85, P<0.05), leukopenia (RR = 0.25, 95%CI: 0.08~0.77, P<0.05) and infection (RR = 0.54, 95%CI: 0.32~0.92, P<0.05), without increased risk of gastrointestinal reaction, rash or herpes zoster infection. Conclusions Leflunomide is a promising therapy for LN treatment, primarily because of the comparable efficacy and favorable safety profile determined by this meta-analysis of RCTs. Larger RCTs with longer duration of observation are necessary to provide strong evidence of the efficacy and safety of leflunomide in LN patients.